2013
DOI: 10.2174/1573406411309040009
|View full text |Cite
|
Sign up to set email alerts
|

Computer Aided Discovery of Potential Anti-inflammatory (S)-naproxen Analogs as COX-2 Inhibitors

Abstract: A series of substituted 2-(6-methoxynapthalen-2-yl) propanoic acid (naproxen) analogs were synthesized. (S)- naproxen (1) was treated with thionyl chloride to yield acid chloride (2) which was then reacted with different heterocyclic moieties and aryl acids to yield the (S)-naproxen analogs (3a-k). All the compounds were screened for antiinflammatory activity using in vivo rat paw oedema model and most of the active ones were investigated for their ulcerogenic potential. In silico studies (molecular modeling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…complex, the docking procedure with the lowest root-mean square deviation (RMSD) was used [35], MOE observed the (Ligand-COX-2) complexes with an RMSD root-mean-square deviation of atomic positions range of (1.119587A°-1.991136) for compounds 5-20. The results of (table 1) show that all compounds had accurate binding energies (RMSD< 1 °A), with the exception of acetyl derivatives (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which had significant RMSD (RMSD > 1°A) for binding energies (table 1). The binding-interaction has improved by adding hydrazide moiety to the orginal compound.…”
Section: Chemistrymentioning
confidence: 98%
See 3 more Smart Citations
“…complex, the docking procedure with the lowest root-mean square deviation (RMSD) was used [35], MOE observed the (Ligand-COX-2) complexes with an RMSD root-mean-square deviation of atomic positions range of (1.119587A°-1.991136) for compounds 5-20. The results of (table 1) show that all compounds had accurate binding energies (RMSD< 1 °A), with the exception of acetyl derivatives (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which had significant RMSD (RMSD > 1°A) for binding energies (table 1). The binding-interaction has improved by adding hydrazide moiety to the orginal compound.…”
Section: Chemistrymentioning
confidence: 98%
“…Thus, we can able to safe retention of these compounds without any effect [37]. All compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) were displayed positivity acceptance for blood brain barrier. Permeability of compounds through blood brain barrier (BBB) indicated that these compounds may be effective in treating inflammation.…”
Section: Onmentioning
confidence: 99%
See 2 more Smart Citations
“…With this theory, we are reporting the synthesis, characterization and biological evaluation of title compounds for their acute and chronic anti-inflammatory activity as well as their ulcerogenic potential. In this study we have used Autodock 4.2 (Morris et al, 2009) for docking of the synthesized compounds on COX-2 crystal structure (PDB: 3NT1) with (Duggan et al, 2010) binding site which was also previously reported by many authors (Raghavendra et al, 2011, Raghavendra et al, 2013, Basile et al, 2012) Additionally we also have calculated and compared the binding affinities of these compounds with standard reference molecules.…”
Section: Introductionmentioning
confidence: 99%